Cegah Dini Stunting Pada Anak Dengan Pemeriksaan Rutin Antropometri Dan Pemberian Nutrisi Di Desa Manarap Baru - Agustria Vista Dewi; Paul Joae Brett Nito; Erna Sari; Hilma Aulia; Husnul Khotimah; Ilhamsyah; Imro Atussholikha; Jihan Fahira; Karen Ardana Putri; Laila Kotdriah Fitriani; Mohammad Basit; Rian Tasalim (JURNAL SUAKA INSAN MENGABDI (JSIM), 2024)
Stunting is a chronic nutritional problem that is often found in children in Indonesia. The prevalence of stunting in Indonesia is still quite high, namely reaching 32.8% in clowns. Even though there was a decrease in the prevalence of stunting in 2018 for both toddlers and toddlers, it still has not reached the expected target. Stunting can affect a child's physical and mental development, including intelligence and learning ability. To prevent stunting, comprehensive treatment is needed for all parties related to children's growth, namely parents, especially mothers, families, the environment and health workers in monitoring children's growth. Therefore, early prevention of stunting is very important to prevent and overcome this problem. One way to prevent early stunting is through anthropometric measurements. Body weight is an important anthropometric measure and is used in infants and young children. In babies and early childhood, body weight can be used to see the rate of physical growth and nutritional status. Common anthropometric indices used to assess nutritional status are weight for age (WW/U), height for age (TB/U), and weight for height (WW/TB). The aim of the community service is to provide outreach to mothers of children in Manarap Baru village regarding early prevention of stunting in children with anthropometric examinations such as the child's weight and height according to age.